Nursing care to people admitted in emergency for attempted suicide - Mayara Cristine Fontão; Jeferson Rodrigues; Monica Motta Lino; Murielk Motta Lino; Silvana Silveira Kempfer
ABSTRACT Objective: to analyze the nursing care to people admitted in emergency for attempted suicide in the perception of the nursing staff. Method: descriptive and exploratory study, of qualitative approach, developed from semi-structured interviews with eight nurses and eight nursing technicians of the emergency service of a University Hospital in south Brazil. Data analysis was performed through content analysis. Results: three categories emerged: nursing care to the person who attempted suicide; the adult emergency service as a scenario of mental health practices; and permanent education-related needs in mental health Final considerations: initiatives capable to potentialize good practices in mental health care are still incipient and lack encouragement in the health service. There is an urgent need to think about changes in the care culture of the emergency service, especially to ensure the scope of psychosocial care actions.